2012
DOI: 10.3133/sir20125111
|View full text |Cite
|
Sign up to set email alerts
|

Sediment loads in the Red River of the North and selected tributaries near Fargo, North Dakota, 2010--2011

Abstract: Natural-resource agencies are concerned about possible geomorphic effects of a proposed diversion project to reduce the flood risk in the Fargo-Moorhead metropolitan area. The U.S. Geological Survey in cooperation with the U.S. Army Corps of Engineers collected data in the spring of 2010 and 2011, and from June to November 2011, during rainfall-runoff events and base-flow conditions to provide information on sediment transport. The data were used to examine sediment concentrations, loads, and particle-size dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Under open‐surface condition, the obtained values of z 0 can vary from 1.0 × 10 −4 m to the order of 10.0 m. This variability agrees with other field studies in literature (Petrie & Diplas, 2016; Petrie et al., 2013). In particular, this range of obtained z 0 does not agree with the measured sediment grain size at the site, which has d 50 ≈ 0.5 mm (Galloway & Nustad, 2012). In ice‐covered case, our estimation for z 0 varies from 1.0 × 10 −7 to 2.03 m as shown in Table 4 for ice roughness.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Under open‐surface condition, the obtained values of z 0 can vary from 1.0 × 10 −4 m to the order of 10.0 m. This variability agrees with other field studies in literature (Petrie & Diplas, 2016; Petrie et al., 2013). In particular, this range of obtained z 0 does not agree with the measured sediment grain size at the site, which has d 50 ≈ 0.5 mm (Galloway & Nustad, 2012). In ice‐covered case, our estimation for z 0 varies from 1.0 × 10 −7 to 2.03 m as shown in Table 4 for ice roughness.…”
Section: Discussionmentioning
confidence: 75%
“…The distribution shows that d 50 = 0.5 mm. The value of d 84 is computed from the USGS field survey data as d 84 ≈ 2.088 mm (Blanchard et al., 2011; Galloway & Nustad, 2012). U x and U y are the two components of the depth‐averaged velocity vector ()U $\left(\vec{U}\right)$ along the X and Y , respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional suspended-sediment samples were collected in 2012 at Fargo as part of a separate sediment collection program. Techniques used for the sediment data collection and analysis are described in Blanchard and others (2011) and Galloway and Nustad (2012).…”
Section: Discrete Water-quality Samplingmentioning
confidence: 99%
“…Studies in the Red River watershed indicate that SSC and streamflow may be correlated poorly. Blanchard and others (2011) andGalloway and Nustad (2012) collected SSC and streamflow data at sites in the Red River watershed near Fargo, North Dakota, during the 2010 and 2011 spring highflow events and during the summer of 2011. Their evaluations of the relation between SSC and streamflow indicated that only two of the six sites sampled during the 2010 spring runoff event had significant relations.Results of the SLR analysis between SSC and streamflow presented in table 5 provide a quantitative description of the plots shown in figure 8.…”
mentioning
confidence: 99%